Analysis Of Food Security, Social Health, Environmental And Household Food Security On Stunting Incidence Of Children Aged 12-59 Months In Coastal Households In Bengkulu Province - Yuliantini, Emy; Sukiyono, Ketut; Sulistyo, Bambang; Yuliarso, M. Zulkarnain; Martiana, Dinda (Universitas Airlangga, 2024)
The natural wealth of coastal areas is not accompanied by the welfare of the people who occupy a lower economic stratum than other land communities, including in fulfilling nutrition. The study aims to analyze the influence of food security and social, health, environmental and household food security factors on the incidence of stunting in children aged 12-59 months in coastal households in Bengkulu Province. The research methodology used a mixed approach, between quantitative and qualitative. Data analysis used Structural Equation Modeling (SEM). The study results showed that the policy aspect significantly affected food security (β=0.085; t=1.979; and p-value < 0.05) but is non-significant on stunting. There was a significant positive effect of health on food security with a value of β=0.237, value t = 7.157, and p-value <0.05. Health had no significant effect on stunting with a value of β=-0.040, value t = 0.963, and p-value > 0.05. Environmental aspects had a substantial adverse impact on food security (β=-0.492; t=12.846; and p-value <0.05) and a significant positive effect on stunting (β=0.155; t=2.781; and p-value < 0.05). The social aspect had a non-significant relationship with both food security and stunting. Food security was significantly related to stunting (β=0.441; t=7.971; and p-value <0.05). The research conclusion is that food security had a significant favorable association with stunting.